2017
DOI: 10.1021/acsami.6b16444
|View full text |Cite
|
Sign up to set email alerts
|

Facile Adhesion-Tuning of Superhydrophobic Surfaces between “Lotus” and “Petal” Effect and Their Influence on Icing and Deicing Properties

Abstract: Adhesion behavior of superhydrophobic (SH) surfaces is an active research field related to various engineering applications in controlled microdroplet transportation, self-cleaning, deicing, biochemical separation, tissue engineering, and water harvesting. Herein, we report a facile approach to control droplet adhesion, bouncing and rolling on properties of SH surfaces by tuning their air-gap and roughness-height by altering the concentrations of poly dimethyl-siloxane (PDMS). The optimal use of PDMS (4-16 wt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…Recently, great attention in the scientific community has been paid to the design of engineered wettability surfaces [ 1 ] due to their potential applications in a wide variety of industrial applications such as air filtration [ 2 , 3 ], oil/water separation [ 4 , 5 , 6 ], anti-icing [ 7 , 8 ], antibacterial [ 9 ], self-cleaning [ 10 ] or even corrosion resistance surfaces [ 11 ], among others. Multiple biological surfaces can be found in nature which exhibit a superhydrophobic behavior such as lotus leaves, duck feathers, or legs of the water strider and due to this, the development of bioinspired superhydrophobic surfaces is a continuous challenge [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great attention in the scientific community has been paid to the design of engineered wettability surfaces [ 1 ] due to their potential applications in a wide variety of industrial applications such as air filtration [ 2 , 3 ], oil/water separation [ 4 , 5 , 6 ], anti-icing [ 7 , 8 ], antibacterial [ 9 ], self-cleaning [ 10 ] or even corrosion resistance surfaces [ 11 ], among others. Multiple biological surfaces can be found in nature which exhibit a superhydrophobic behavior such as lotus leaves, duck feathers, or legs of the water strider and due to this, the development of bioinspired superhydrophobic surfaces is a continuous challenge [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the difference between these two evaporation behaviors is the pinning of the water droplets onto the contact region of the water droplet. The hybrid high-adhesive surfaces form the continuous TCL, even at high CAs, from covering the surface cavities conformally by water 18,[21][22][23] , resulting in the contact line hardly receding by the pinning of the contact line along the surface of the WZ wetting micro-wall. On the other hand, as the TCL becomes discontinuous on the low-adhesive surfaces, resulting in reduced water contact area in micro or nanoscale 19,20 , the water droplets can easily evaporate while retaining their spherical shape due to the receding of the contact line without pinning during evaporation in the steady CB wetting state.…”
Section: Superhydrophobicity With the Tunable Water Adhesion On The Hmentioning
confidence: 99%
“…Research has revealed that, as the TCL becomes discontinuous by lowering the contact area due to micro or nanoscale features and the scale of individual TCL becomes smaller, the air-pocket between the structures becomes stable, decreasing the water adhesion 19,20 . Conversely, certain surfaces form the high water adhesion, even at high CAs, with water penetrating through the surface cavities to increase the contact area, ultimately resulting in the formation of the continuous TCL 18,[21][22][23] . These findings underscore the importance of appropriately selecting the required structure and its smart combination, such as the hierarchical or hybridized structures, to control the adhesion of the superhydrophobic surfaces.…”
mentioning
confidence: 99%
“…9,10 Besides basic studies on icing, many anti-icing methods are proposed to suppress the ice accretion, one of which is the application of nanoengineered surfaces. 11,12 Researchers fabricated numerous surfaces with various structures and wettability with the purpose of delaying the ice nucleation, [13][14][15] retarding the ice propagation, 16,17 reducing the ice adhesion, 18,19 and even self-cleaning subcooled droplets or melting frost by a kind of self-jumping behavior, [20][21][22][23][24][25] and have achieved expected results.…”
Section: Main Textmentioning
confidence: 99%